The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1109/tcomm.2019.2940659
|View full text |Cite
|
Sign up to set email alerts
|

The Meta Distribution of the SIR in Linear Motorway VANETs

Abstract: The meta distribution of the signal-to-interferenceratio (SIR) is an important performance indicator for wireless networks because, for ergodic point processes, it describes the fraction of scheduled links that achieve certain reliability, conditionally on the point process. In this paper, we calculate the moments of the meta distribution in vehicular ad hoc networks (VANETs) along high-speed motorways. Due to the high speeds, the drivers maintain large safety distances, and the Poisson point process (PPP) bec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 31 publications
(78 reference statements)
0
11
0
Order By: Relevance
“…Otherwise, to draw valid conclusions about the network's performance the road intersections must be explicitly modeled [16]. For motorway VANETs, on the contrary, the superposition of onedimensional (1D) point processes is sufficient [23]- [25].…”
Section: B Motivation and Prior Artmentioning
confidence: 99%
See 1 more Smart Citation
“…Otherwise, to draw valid conclusions about the network's performance the road intersections must be explicitly modeled [16]. For motorway VANETs, on the contrary, the superposition of onedimensional (1D) point processes is sufficient [23]- [25].…”
Section: B Motivation and Prior Artmentioning
confidence: 99%
“…Path distance distributions on a real map for 15 intersection points, see Fig.10a. 'Blue' lines are simulations, 'red' lines correspond to Algorithm 1 and 'black' lines to the two-dimensional PPP model, see equation(23). 2 500 simulation runs.…”
mentioning
confidence: 99%
“…It is shown that the MD is bimodal, i.e., the individual link success probabilities are either low or high, not concentrated near their average. The MD of the SIR in linear motorways is analyzed in [23] using a model where the inter-vehicle distances follow the shifted-exponential probability density function.…”
Section: Related Workmentioning
confidence: 99%
“…Authors of [11] exploited the SIR MD to adjust the per-link reliability via rate control. The MD is further used in [12] to describe the behavior of linear motorway vehicular ad hoc networks, where the vehicles' high speed makes the Poisson point process not suitable for system modeling. In [13], the MD allows the authors to optimize the power allocation in downlink NOMA with and without latency constraints.…”
Section: Introductionmentioning
confidence: 99%